‘Under the influence’. The fight against the 'evil drink' in nineteenth-century England - Paisana, Joanne (2000)
This chapter, based on research for my PhD thesis, examines the excessive drinking of alcoholic beverages in nineteenth-century England, especially by the working classes, and the attempts by the temperance societies to combat it. The reasons for excessive drinking, the 'discovery' of the alcohol abuse problem and the development of the temperance movement in England are appraised.